2016
DOI: 10.1016/j.jconrel.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of blood coagulation factor X-binding to Ad5 by position-specific PEGylation: Preventing vector clearance and preserving infectivity

Abstract: The biodistribution of adenovirus type 5 (Ad5) vector particles is heavily influenced by interaction of the particles with plasma proteins, including coagulation factor X (FX), which binds specifically to the major Ad5 capsid protein hexon. FX mediates hepatocyte transduction by intravenously-injected Ad5 vectors and shields vector particles from neutralization by natural antibodies and complement. In mice, mutant Ad5 vectors that are ablated for FX-binding become detargeted from hepatocytes, which is desirabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 50 publications
0
36
1
Order By: Relevance
“…Using the increase in liver-directed gene transfer as an indirect readout of disruption of HAdv-Kupffer cell interactions, it was also demonstrated that targeted shielding of HAdv-C5 virion surface by attaching small molecular weight polyethylene glycol (PEG) to hexon HVRs (HVR1, HVR2, HVR5, or HVR7) is sufficient to increase virus-mediated hepatocyte transduction after intravenous virus administration [46]. Using the approach of targeted shielding of hexon HVR loops with PEG, Krutzke et al [48] demonstrated that modification of hexon HVR1 loop in HAdv-C5 is sufficient to prevent virus interaction with natural antibodies and complement, leading to an increase in hepatocyte transduction. The same group reported that intravenous administration of HAdv-C6 or HAdv-C5-based vector with all hexon HVRs mutated for those of HAdv-C6 (Ad5/6GL) resulted in a highly efficient hepatocyte transduction.…”
Section: Mechanisms Of Hadv Sequestration In Tissue Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the increase in liver-directed gene transfer as an indirect readout of disruption of HAdv-Kupffer cell interactions, it was also demonstrated that targeted shielding of HAdv-C5 virion surface by attaching small molecular weight polyethylene glycol (PEG) to hexon HVRs (HVR1, HVR2, HVR5, or HVR7) is sufficient to increase virus-mediated hepatocyte transduction after intravenous virus administration [46]. Using the approach of targeted shielding of hexon HVR loops with PEG, Krutzke et al [48] demonstrated that modification of hexon HVR1 loop in HAdv-C5 is sufficient to prevent virus interaction with natural antibodies and complement, leading to an increase in hepatocyte transduction. The same group reported that intravenous administration of HAdv-C6 or HAdv-C5-based vector with all hexon HVRs mutated for those of HAdv-C6 (Ad5/6GL) resulted in a highly efficient hepatocyte transduction.…”
Section: Mechanisms Of Hadv Sequestration In Tissue Macrophagesmentioning
confidence: 99%
“…Specifically, although shielding oncolytic HAdv with PEG or protein conjugates significantly increases the efficacy of oncolytic HAdvbased vectors in mouse models [130,132], after the initial round of replication, the progeny of oncolytic virus produced in tumor sites would not be covered with PEG or protein shields, thus exposing the virus to receptors and cells of the innate immune system. Moreover, certain cytokines, most notably IL-6 and IL-12, still remain elevated after systemic delivery [134] or direct blood cell exposure to PEGylated HAdv vectors [48], demonstrating that any single-pronged approach to avoiding virus recognition by the innate immune system is unlikely to prevent or alleviate all factors and mechanisms responsible for triggering multifaceted host innate immune and inflammatory responses to HAdv.…”
Section: Complexity Of Designing Hadv Vectors With Reduced Innate Immmentioning
confidence: 99%
“…For final production, approximately 1 × 10 8 to 5 × 10 8 cells were harvested as described above and the pellet was re‐suspended in 3 ml of HEPES buffered saline (50 mM HEPES, 150 mM NaCl, pH 8). For vector purification, cesium‐chloride (CsCl) gradient centrifugations were performed as described previously …”
Section: Methodsmentioning
confidence: 99%
“…Life cycle deficiency and absence of vector propagation as a result of reversion of the introduced mutations was confirmed by three serial rounds of re‐infection in non‐complementing A549 cells using different amounts of non‐purified virus. Physical vector titers were determined as described previously …”
Section: Methodsmentioning
confidence: 99%
“…The researchers subsequently showed that replacing the FX shield with a polyethylene glycol shield prevented macrophages from neutralizing the vector in vitro and demonstrated significantly improved transduction in murine models (22). These findings suggest that such shielding could greatly improve the clinical efficiency of Ad5 in human gene therapies.…”
Section: Developing and Assessing Non-clinical Models And Methods Prementioning
confidence: 99%